Basic Education Innovation: Enhancing Teacher Competence at SDN 1 Kedungdowo through Learning and Gamified Quizizz - Miftahus Surur; Arico Ayani Suparto; Ahmad Zaki Emyus; Siti Karunia Dewi; Zeinul Mursidin (GUYUB: Journal of Community Engagement, 2025)
This community service activity entitled Deep Learning Implementation Training Integrated with Quizizz-Based Learning Games was carried out at SDN 1 Kedungdowo Arjasa Situbondo in response to the limited mastery of technology-based learning media among teachers. The program aimed to improve teacher competence in utilizing innovative digital platforms to create more engaging and effective learning. The method used was Participatory Action Research (PAR), which emphasized collaboration and active involvement of teachers in every stage. The process began with identifying problems and needs, followed by training through theoretical materials on deep learning concepts and hands-on practice in developing Quizizz-based learning games. The implementation was then observed through classroom practice and teacher performance monitoring, and finally reflected through joint discussions to evaluate achievements and challenges as well as to design sustainable follow-up strategies.The results showed significant improvements in teacher competencies. Based on evaluation data, teachers’ understanding of deep learning concepts increased by an average of 78%, while their ability to design and apply Quizizz-based learning games rose by 85%. Classroom observations also demonstrated a 70% increase in student engagement, indicating that the integration of technology-based media successfully enhanced the learning atmosphere. Teachers expressed greater confidence in using digital tools, proving that the activity met its competency targets